Orthostatic intolerance in post-concussion patients. Issue 5 (3rd September 2022) - Gould, Sara J.; Cochrane, Graham D.; Johnson, Jarvis; Hebson, Camden L.; Kazamel, Mohamed
ABSTRACT: Orthostatic intolerance (OI) following pediatric concussion is not well understood. Assessing the prevalence of concussion-related OI and how it compares to non-concussion-related OI will improve care for patients suffering with these symptoms. OBJECTIVE: We set out to describe concussion-related OI in adolescence, with particular emphasis on time to recovery and differences from non-concussion-related OI (including male vs. female prevalence). Retrospective chart reviews were completed on post-concussion patients endorsing symptoms of OI. The patients' sex, sport history, previous concussions, time since injury, and recovery time were analyzed and compared between males and females as well as against general OI statistics. Thirty-nine pediatric patients, representing 8.7% of all new patients referred to a specialized concussion clinic over a 13-month interval, were included in the chart review. Mean age of onset was 15.0 ± 2.5 years and 18 (46%) were males. The median times from evaluation to symptom resolution were 120 days. Of 18 patients who completed head-up tilt table testing, 17 (94%) had orthostatic tachycardic response (>40 bpm heart rate increment). Post-concussive OI differs from other orthostatic intolerance etiologies, lacking a strong female predominance and exhibiting a shorter time course to recovery compared to other etiologies of OI (but longer recovery time compared to concussion patients in general). Clinical orthostatic vital signs may not be sensitive for diagnosing orthostatic intolerance in athletes, likely due to higher vagal tone and more efficient skeletal muscle pump.